Dry Media Formulation to Increase Productivity and Quality of Silkworms (Tubifex sp.) as A Natural Feed Development for Aquaculture - Corne, Yohanes; Rahardjo, Sinung; Nurhudah, Moch.; Wiradana, Putu Angga (Jurnal Perikanan Universitas Gadjah Mada, 2024)
Silk worms (Tubifex sp.) are a type of natural food that is widely used for the needs of fish farming activities, especially in the freshwater fish hatchery phase. This study aimed to determine the effect of providing dried feed/media with varying doses on the productivity of silk worms. The study was conducted using a Completely Randomized Design (CRD) with three treatment groups and four replications which included administration of dry media at a dose of (P1) 150 g/m2 (P2) 250 g/m2 (P3) 350 g/m2. The initial silk worm seeds were obtained from silk worm collectors or sellers in Cipayung-East Jakarta. Maintenance of silk worms was carried out for 55 days. The results of the diversity analysis showed that there was a significant difference in the dose of dry media in cultivating silk worms (P≤0.05). The best absolute weight growth, population growth, and productivity were shown in the media treatment with a dose of 250 g/m2 (P2) with absolute biomass growth of 408.7 g, population growth of 209,381 individuals, and productivity of 1.3/m2/cycle. The results of water quality observations are still in a relatively optimal range. Silk worms have the potential to be developed as a safe, environmentally beneficial, and inexpensive natural food for cultivated animals.